THE ROLE OF IL-6 IN THE MANAGEMENT OF MEDICAL TREATMENT OF PATIENTS WITH COVID-19-ASSOCIATED ACUTE RESPIRATORY DISTRESS SYNDROME - Şimşek, Meltem; Yıldırım, Fatma; Tayşi, Muhammed Rıdvan; Karaman, Irem; Bağrıyanık, Zübeyde Lale; Dura, Halil Ibrahim (Journal of Ayub Medical College Abbottabad, 2022)
Background: Many cytokines propose to play a role in the pathogenesis of Severe Acute Respiratory Syndrome Coronavirus type 2 (SARS-CoV-2) associated COVID-19 disease. High interleukin-6 (IL-6) levels are associated with mortality and other poor clinical outcomes in COVID-19. Methods: In this retrospective study, the correlation of IL-6 level with clinical and other inflammatory parameters, its role in treatment change and its relationship with mortality in COVID-19 patients developing acute respiratory distress syndrome (ARDS) were investigated. Results: Totally 76 patients were included in the study; Thirty-four (44.7%) patients were female and 42 (55.3%) patients were male. All patients had IL-6 levels above the upper reference value (>5.9 pg/mL). Overall, 48 patients (63.1%) had a severe clinical presentation (tachypnoea, tachycardia, fever) that was clinically compatible with IL-6 values, and medical treatment was changed for COVID-19 in this group. A positive correlation was detected between IL-6 and CRP on the day of the change in treatment (p=0.035, r=0.76). There was no decrement observed in IL-6 level on the 3rd day in patients that was clinically thought to have cytokine storm and whose treatment was changed. Mortality was higher in the group whose treatment was changed. Conclusion: We believe that IL-6 level alone is insufficient to decide on a change in treatment, and correlation of IL-6 with the patient’s clinical status is more significant in such decision.